Inter-agency Cooperation and Good Tax Governance in Africa - Jude Amos (Pretoria University Law Press (PULP), 2018)
The Institute for Austrian and International Tax Law is one of the global leading tax academic institutions active in the field of international taxation. Its main fields of interest are corporate tax law, international tax law and European tax law and to a growing extent tax policy and transfer pricing. It engages in research and teaching in these areas, its staff participates in numerous national and international tax projects and over the years has developed an impressive network of contacts in more than 90 countries. The Institute's team comprises 60 academic staff members as well as many visiting professors and guest researchers from more than 40 countries. The African Tax Institute (ATI) is devoted to training, research and technical assistance in the areas of tax policy and tax administration on the African continent. Its main goal is to develop capacity in ministries of finance and revenue authorities. Towards this goal, the ATI offers an interdisciplinary Master's in taxation and a PhD in tax policy, primarily to students from the public sector. The main research areas of ATI staff and students include tax policy, international taxation, natural resource taxation, valueadded tax, fiscal decentralisation and property taxation.